Malaysian Development Financial Institutions And Islamic Banks Strategic Direction Setting: A Thematic Review Based On PMMS Performance Model - Norazidah, Shamsudin; Mustafa Omar, Mohammed; Yuserrie, Zainuddin; Azis, Yudi (PalArch Foundation, 2020)
Vision and mission statement is the main reference of a firm which would direct them to the ends that they have set for themselves. For companies who striving in Islamic industry (products and services), fulfillment of Maqasid al-Shariah should be as their main focus in directing them to achieve their success which should contribute to Islamic economic attainment. However, there are studies found that profit-maximization is still to be the dominant direction of Islamic financial institutions. Hence, the study been conducted to assess the direction setting that have been set by Islamic Banks (IBs) and Development Financial Institutions (DFIs) in Malaysia who are among the key players in contributing to the country’s economic development. The study adopt PMMS model in performing the thematic review on DFIs and IBs vision and mission statement. Six DFIs and ten local IBs been included in the study. The study is aiming on identifying the (1) fulfillment and (2) concentration of existing direction setting of Malaysian DFIs and IBs on all three concepts and nine dimensions of Maqasid-al Shariah. It is found that both DFIs and IBs have covered all three themes of Maqasid-al Shariah, however, both types of financial institutions have different concentration on Maqasid concept and thematic direction. Besides on findings of one untagged dimension by both DFIs and IBs, the result of the study is hope to further suggest on the performance evaluation framework of the DFIs and IBs as it should be referred to their own strategic direction setting especially for fulfilment of time-series or vertical analysis for performance evaluation.